WANPRESTASI PENYEWA PADA PEMILIK RUKO DALAM PERJANJIAN SEWA MENYEWA DI DUSUN TANJUNG KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS - NIM. A1012191060, CONSITA FEBIOLA (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstracThe lease agreement for the shophouse in Tanjung Hamlet, Sanatab Village, Sajingan District, Sambas Regency has a period of 1 (one) year, commencing from the date of the agreement on the lease agreement. This is done in writing, accompanied by an upfront payment as cash of the total rental fee determined by the shop owner. But of course it will be a problem if the fulfillment of these rights and obligations does not work as it should, especially in terms of implementation there is bad faith, which comes from one of the parties involved in the agreement, whether it comes from the owner, or the intention of the owner. which is not good from the shophouse tenant who transfers the rented shophouse rental to someone else.Based on the description above, the problems in this research are: